2010
DOI: 10.1177/145749691009900302
|View full text |Cite
|
Sign up to set email alerts
|

Early Complications after Nipple-Sparing Mastectomy and Immediate Breast Reconstruction with Silicone Prosthesis: Results of 214 Procedures

Abstract: Background and Aims: breast reconstruction with silicone prosthesis following nipplesparing mastectomy has become widely accepted as a reconstruction option in women requiring mastectomy for cancer. the purpose of this study was to evaluate the incidence and some factors influencing early local complications in patients undergoing nsm with immediate implant reconstruction.Material and Methods: prospective study was performed on a consecutive series of 214 breast reconstructions in 205 patients. all complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 22 publications
2
62
1
1
Order By: Relevance
“…Concerns are mostly related to increased early postoperative complications such as infection, wound healing problems, and ischemia or necrosis of the skin or NAC [18,19,20]. Age, skin incision, flap thickness, reconstruction type, smoking, neoadjuvant chemotherapy, preoperative irradiation, and comorbidities have been reported as risk factors for ischemic complications concerning the skin and NAC [1,2,3,4,18,19,21,22,23,24,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Concerns are mostly related to increased early postoperative complications such as infection, wound healing problems, and ischemia or necrosis of the skin or NAC [18,19,20]. Age, skin incision, flap thickness, reconstruction type, smoking, neoadjuvant chemotherapy, preoperative irradiation, and comorbidities have been reported as risk factors for ischemic complications concerning the skin and NAC [1,2,3,4,18,19,21,22,23,24,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of contemporary studies, the necrosis rate has been found to be between 0 and 7% (21,22,25,31). In the current study the total necrosis rate was 6%, with 5 (2.5%) patients requiring removal and reconstruction of the NAC due to the extent of necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2010 prospective study of 214 consecutive NSMs with immediate silicone implant reconstruction, the overall complication rate was 16% with 6% requiring explantation of the prostheses due to the complication (22). In 2012 the present study began performing NSM with direct-to-implant reconstruction and in the study period identified no difference in complication rates when a permanent implant was placed at the time of mastectomy in lieu of a tissue expander; however, more patients with direct implant-based reconstruction required removal of their implants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the risk for skin necrosis is increased with SSM/NSM and is described in the literature as occurring at a rate of about 16% [42,43]. To prevent possible skin necrosis, additional risk factors should be ruled out before surgery.…”
Section: Complicationsmentioning
confidence: 99%